KETERAMPILAN SOSIAL: ANALISIS PERILAKU SISWA TERHADAP ORANG LAIN PADA SISWA KELAS 3 SD NEGERI 2 KEBUMEN - Diyani Ayu Karimizzah; Suhartono Suhartono; Ratna Hidayah (Universitas Sebelas Maret, 2020)
AbstractThe challenge in this disruptive era is greater than the previous one, because digitalization and artificial intelligence are growing exponentially. Humans need social skills to sustain existence. A process for acquiring social skills is called socializing. Nowadays, socializing is happening frequently in the virtual world using artificial intelligence. The study aimed to describe the student’s social skills to others and the strategy applied by the teachers and parents in fostering social skills. It was qualitative narrative approach. Data collection techniques were observation, interview, and questionnaires. The subjects were 22 students, parents, and class teacher of third grade of SDN 2 Kebumen. The results of this study indicate the quality of students behavior toward others that of helping, communicating and greeting to others, working in a team, and being empathy. Also, the teacher and the parents met the accomplishment of the strategies of giving instruction, training, and assessment.Keywords: social skill, qualitative description